Internetware: A Software Paradigm for Internet Computing. - Mei, Hong; Huang, Gang; Xie, Tao (Computer (00189162), 2012)
To meet the needs of computing in the Internet environment, the Internetware software paradigm provides a set of technologies that support the development of applications with characteristics that are autonomous, cooperative, situational, evolvable, emergent, and trustworthy.